Α-Glucosidase inhibitory activities of phenolic acid amides with l-amino acid moiety12. Issue 56 (24th May 2016) - Liu, Bin; Ma, Ji-Mei; Chen, Hang-Wei; Li, Zi-Long; Sun, Lin-Hao; Zeng, Zhen; Jiang, Hong
Abstract : Phenolic acid amides with al -amino acid moiety showed excellent inhibitory activity on α-glucosidase. Abstract : α-Glucosidase inhibitors can effectively control postprandial hyperglycemia. In this study, a series of phenolic acids with thel -amino acid moiety were synthesized and their inhibitory activities against α-glucosidase from Saccharomyces cerevisiae (EC 3.2.1.20) were evaluated. The results suggested that all these compounds showed strong α-glucosidase inhibitory activities. In particular, N -(4-hydroxyl-phenylpropenoyl)-l -alanine (c2 ) and N -(4-hydroxyl-phenylpropenoyl)-l -methionine (c8 ) exhibited much higher potency (IC50 values 0.04 mM) than the positive control, acarbose (IC50 values 1.70 mM). Three-dimensional quantitative structure–activity relationship (3D-QSAR) model for comparative molecular field analysis (CoMFA) was generated and the result showed that bulk groups and high electron density groups on the amino acid residues were a benefit to their activities. Moreover, the substituents with low electron density and little steric hindrance on the para position of the benzene ring were helpful in improving the activities. Kinetic analysis indicated that compound (c2 ) acted as a mixed-type inhibitor with a K i value of 0.0124 mM. Docking analysis showed that they could bind to α-glucosidase at the catalytic site via hydrogen bonds and a π–π stacking.